An Update on the Use of Alginate in Additive Biofabrication Techniques - Gill, Amoljit S.; Deol, Parneet Kaur; Kaur, Indu Pal (Current Pharmaceutical Design, 2019)
Background: Solid free forming (SFF) technique also called additive manufacturing process is immensely popular for biofabrication owing to its high accuracy, precision and reproducibility. Method: SFF techniques like stereolithography, selective laser sintering, fused deposition modeling, extrusion printing, and inkjet printing create three dimension (3D) structures by layer by layer processing of the material. To achieve desirable results, selection of the appropriate technique is an important aspect and it is based on the nature of biomaterial or bioink to be processed. Result & Conclusion: Alginate is a commonly employed bioink in biofabrication process, attributable to its nontoxic, biodegradable and biocompatible nature; low cost; and tendency to form hydrogel under mild conditions. Furthermore, control on its rheological properties like viscosity and shear thinning, makes this natural anionic polymer an appropriate candidate for many of the SFF techniques. It is endeavoured in the present review to highlight the status of alginate as bioink in various SFF techniques.
Keywords: bioink